An analysis of parents’ perceived stress and the parent-child relationship during the COVID-19 pandemic - Tarsuslu, Bedia; Sahin, Ayse; Durat, Gulgun; Arikan, Duygu (Bangladesh Journal of Medical Science, 2021)
Objectives: The measures taken by governments to prevent the spread of COVID-19 have changed millions of people’s daily lives. This study analyzes parents’ perceived stress and parent–child relationship while staying home due to lockdown during the COVID-19 pandemic. Methods: The sample for this descriptive and cross-sectional study comprised 521 parents with children aged 4–18 years. Data were collected online using a Personal Information Form, the Perceived Stress Scale (PSS-4), and Child Parent Relationship Scale (CPRS) between 2 and 27 April 2020 in Turkey. Findings: The mean age of the study participants was 38.98±6.578 years, and 53.2% of participants were female. The parents’ mean PSS-4 and CPRS scores were 8.45±2.37 and 53.62±11.71, respectively. Of the parents, 44.0% stated that the days spent in the “Staying Home” period strengthened their relationships with their children, and 56.4% thought that it had provided them with the opportunity to take better care of their child. Mothers’ mean CPRS conflict scores were significantly higher than those of the fathers, and a negative relationship was found between the PSS-4 and CPRS positive-relationship sub-dimensions. Conclusion: Psychosocially supporting interventions should be planned for parents, especially mothers, who hold the most responsibility concerning housework and childcare during situations affecting the life adversely. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.97-107